(untitled) (Journal of actual problems of jurisprudence, 2024)
In this article, we will consider the lease agreement for commercial premises in the system of Legal Sciences from the point of view of scientific and theoretical study. In the system of modern legal sciences, we determine the need for a scientific and theoretical study of the lease agreements of commercial premises by the following factors. Because: first of all, the object of study of the article is primarily studied by civil law within the system of Legal Sciences; secondly, in addition to the above-mentioned branch of law, other branches and institutions of the legal system are studied, in particular, contract law, Lease Law, Business Law, housing law, Construction Law, Land Law, private international law, etc; thirdly, experts are interested in the study of this topic in addition to these branches of law, which are now traditionally developed legal institutions of civil law, such as "property law", "property law", as well as "property law". Therefore, these branches of law and other legal institutions included in the system of Legal Sciences have a direct right to study in scientific and theoretical terms the lease agreement of these commercial premises. A comprehensive analysis of these issues will allow identifying existing problems and suggesting ways to solve them, which will contribute to the development of legal regulation in this area and ensuring a balance of interests between landlords and tenants. Keywords: property, property, rental, commercial premises.